2019
DOI: 10.1038/s41598-019-54225-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ω-3 polyunsaturated fatty acids on the liver lipidome, proteome and bile acid profile: parenteral versus enteral administration

Abstract: Parenteral nutrition (PN) is often associated with the deterioration of liver functions (PNALD). Omega-3 polyunsaturated fatty acids (PUFA) were reported to alleviate PNALD but the underlying mechanisms have not been fully unraveled yet. Using omics´ approach, we determined serum and liver lipidome, liver proteome, and liver bile acid profile as well as markers of inflammation and oxidative stress in rats administered either ω-6 PUFA based lipid emulsion (Intralipid) or ω-6/ω-3 PUFA blend (Intralipid/Omegaven)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 58 publications
2
12
0
2
Order By: Relevance
“…Physiological BAs spectrum. All these findings may contribute to the explanation of ω-3 PUFA protective effects in the context of PN [37].…”
Section: Mechanisms Of Lipid Toxicity Observed In Laboratory Animals mentioning
confidence: 69%
See 1 more Smart Citation
“…Physiological BAs spectrum. All these findings may contribute to the explanation of ω-3 PUFA protective effects in the context of PN [37].…”
Section: Mechanisms Of Lipid Toxicity Observed In Laboratory Animals mentioning
confidence: 69%
“…Bechynska et al in an effort to understand the underlying mechanism of PNALD took a different approach and determined serum and liver lipidome, liver proteome, liver bile acid profile as well as markers of inflammation oxidative stress in rats admin-istered either ω-6 PUFA based lipid emulsion (Intralipid) or ω-6/ω-3 PUFA blend (Intralipid/Omegaven) via the enteral or parenteral route in rats [37]. They showed that PN administered omega-3 polyunsaturated fatty acids (ω-3 PUFA), compared with parenterally administered Intralipid, and was associated with 1.…”
Section: Mechanisms Of Lipid Toxicity Observed In Laboratory Animals mentioning
confidence: 99%
“…The total malondialdehyde concentration in the plasma was determined after alkaline hydrolysis with sodium hydroxide using the liquid chromatography-tandem mass spectrometry (LC-MS/MS) method according to Bechynska et al [17].…”
Section: Determination Of Malondialdehyde Concentration In Plasmamentioning
confidence: 99%
“…EPA and DHA are proving to be increasingly versatile in their benefits with newer research which broadens the spectrum of their actions through modes of administration other than oral. In a study conducted by Bechynska et al (2019) a dietary formulation of n‐3 fatty acids versus n‐6 fatty acids was administered enterally and parenterally, to compare the effects on liver lipidome and BA profile, as an effort to understand the protective role of n‐3 fatty acids in parenteral nutrition. Although, it was concluded that although the inclusion of n‐3 fatty acids in the nutrition mixtures facilitated prevention and reversal of liver disease associated with parenteral nutrition, the mechanisms for these benefits remain unknown.…”
Section: Influence Of N‐3 Fatty Acids On Ba Signaling Pathwaysmentioning
confidence: 99%